1993
DOI: 10.1111/j.1348-0421.1993.tb03237.x
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Correlation between the Precursor Frequency of Cytotoxic Lymphocytes to Autologous Epstein‐Barr Virus‐Transformed B Cells and Antibody Titer Level against Epstein‐Barr Virus‐Associated Nuclear Antigen in Healthy Seropositive Individuals

Abstract: A limiting dilution analysis was established to determine the precursor frequency (PF) of cytotoxic lymphocytes against autologous B cells transformed with the Epstein‐Barr virus (EBV). This method was found to detect mainly self‐restricted T‐cell activity and little non‐self‐restricted cytotoxicity. The mean PF in 21 healthy EBV‐seropositive persons was 1.4 × 10‐3 (range: 0.03 × 10‐3 to 8.7 × 10‐3) for peripheral blood mononuclear cells, whereas 4 samples of mononuclear cells obtained from umbilical cord bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Although an increase in EBV antibody titers is observed in other EBV-related conditions, a specific increase in anti-EBNA-1 and the anti-EBNA complex without a concomitant increase in anti-VCA is unique to MS and is consistent with the hypothesis of T-cell hyperreactivity because anti-EBNA-1 titers are positively correlated with T-cell function. 14 Overall, the results of these studies are consistent with the hypothesis that elevations in the anti-EBNA complex and anti-EBNA-1 titers in individuals who develop MS occur in the late teenage years or early 20s and may precede the time of onset of MS symptoms by 10 years or more. This hypothesis needs to be tested in further studies including teenagers and young adults.…”
Section: Commentsupporting
confidence: 81%
“…Although an increase in EBV antibody titers is observed in other EBV-related conditions, a specific increase in anti-EBNA-1 and the anti-EBNA complex without a concomitant increase in anti-VCA is unique to MS and is consistent with the hypothesis of T-cell hyperreactivity because anti-EBNA-1 titers are positively correlated with T-cell function. 14 Overall, the results of these studies are consistent with the hypothesis that elevations in the anti-EBNA complex and anti-EBNA-1 titers in individuals who develop MS occur in the late teenage years or early 20s and may precede the time of onset of MS symptoms by 10 years or more. This hypothesis needs to be tested in further studies including teenagers and young adults.…”
Section: Commentsupporting
confidence: 81%
“…Notably, the MS-associated EBNA-1 394-451 region identified encompasses several immunodominant HLA DR-, including potential HLA DRB1*1501-restricted CD4 + Tcell epitopes. 31,32 Moreover, MS patients have elevated frequencies and broader epitope reactivity of EBNA-1-specific CD4 + T-cells 32 , including specific T-cells that cross-reacted with MS-associated myelin proteins. [26][27][28][29][30][31][32][33] We hypothesize that in genetically predisposed individuals 1,34 , EBNA-1 expression evokes a neuroantigen cross-reactive anti-EBNA-1 T-cell response, that upon entry into the CNS recognizes and target cells expressing the cognate neuroantigen.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 It has also been reported that self-antigen-specific T cells, for any particular protein, are usually present at frequencies of 10 Ϫ5 cells-approximately 100-fold more rare than virusspecific T cells. 39,40 Therefore, when we use approximately 10 7 T cells for stimulation in our assays, it is mathematically possible to generate anywhere from 10 5 to 10 9 antigen-specific T cells in a 1-week expansion. In any case, our data strongly support that AAV-loading-derived CTLs are antigen/HM1.24 specific.…”
Section: Discussionmentioning
confidence: 99%